2017
DOI: 10.1001/jama.2017.16191
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Prepregnancy Body Mass Index and Severe Maternal Morbidity

Abstract: Among pregnant women in Washington State, low and high prepregnancy BMI, compared with normal BMI, were associated with a statistically significant but small absolute increase in severe maternal morbidity or mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(87 citation statements)
references
References 30 publications
6
73
0
1
Order By: Relevance
“…hBAT activation capacity was reduced in obese subjects [12, 16]. Furthermore, it was demonstrated that the reduced ADRB3 expression in adipose tissue of obese rats [9, 10] increased after weight loss following Roux-en-Y gastric bypass surgery [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hBAT activation capacity was reduced in obese subjects [12, 16]. Furthermore, it was demonstrated that the reduced ADRB3 expression in adipose tissue of obese rats [9, 10] increased after weight loss following Roux-en-Y gastric bypass surgery [25].…”
Section: Discussionmentioning
confidence: 99%
“…BMI was calculated as weight (kilograms) divided by height (meters) squared. Participants were divided into two subgroups according to BMI: normal-weight group (NW group; BMI < 25 kg/m 2 ) and overweight group (OW group; (25 ≤ BMI < 30 kg/m 2 ) [12]. This study was conducted in terms of Declaration of Helsinki and approved by the local Ethical and Research Committee of Jinan Central Hospital (Shandong, China).…”
Section: Methodsmentioning
confidence: 99%
“…[ 11 ] A population-based retrospective cohort study over a 10-year period (2004–2013) in Washington State showed that there were statistically significant increases in risk of severe maternal morbidity among women with obesity. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Compared to normal weigh women, obese women are also more likely to have a stillbirth (odds ratio 5.2, 95% CI 2.5-10.9) or perinatal death, particularly in later gestations (Hazard ratios (95% CI) for foetal death before week 14: 0.8 (0.5-1.4), weeks 14-19: 1.6 (1.0-2.5), weeks 20-27: 1.9 (1.1-3.3), weeks 28-36: 2.1 (1.0-4.4), weeks 37-39: 3.5 (1.9-6.4) and weeks 40+: 4.6 (1.6-13.4) (Nohr et al 2005). There is a dose-response relationship between maternal pre-pregnancy weight and severe maternal morbidity or mortality (Lisonkova et al 2017). The absolute increases in numbers of deaths or cases of serious morbidity per 10,000 women were 17.6 for overweight women, and 24.9, 35.8 and 61.1 for women with obesity classes 1, 2 and 3, respectively.…”
Section: Obesity and Maternal Health In Pregnancy And In The Longer Termmentioning
confidence: 98%